Evolution of Xylariomycetidae (Ascomycota: Sordariomycetes) - M. C. Samarakoon (2018)
© Guizhou Academy of Agricultural Sciences. The class Sordariomycetes, which is the second largest class in the phylum Ascomycota, comprises highly diversified fungal groups, with relatively high substitution and evolutionary rates. In this preliminary study, divergence estimates of taxa of Xylariomycetidae are calculated using Ophiocordyceps fossil evidence and secondary data. The combination of fossil and secondary calibration can affect the divergence time estimates by pushing the ages towards the roots. The estimated divergence of Hypocreomycetidae, Lulworthiomycetidae and Xylariomycetidae occurred during the Early Mesozoic (201-252 Mya) and Diaporthomycetidae and Sordariomycetidae occurred later during the Late Mesozoic (145-252 Mya). Two characteristic divergence groups have evolved 168 and 147 Mya and probably provide additional evidence for continuation and species richness of the orders Amphisphaeriales and Xylariales. The early diversifications of the families in Xylariomycetidae have occurred during the Early Cretaceous (100-145 Mya).